Efficiency of Dual Functional Fat, Oil and Grease (FOG) Trap in Treating Kitchen Wastewater - Ibrahim Idham, Siti Nur Fatehah (Progress in Engineering Application and Technology, 2021)
Direct drainage into the sewerage system of untreated kitchen wastewater created from the commercial restaurant leads to many adverse ecosystem effects due to disposal into the environment. FOG enters the sewer system from restaurants, residences, and food facilities in the industry. Its release into the sewer system results in a continuous build-up causing eventual sewer pipes blockage. These FOG blockages contribute to sanitary sewer overflows, flooding of property and water bodies polluted with sewage. As a type of renewable natural plant, kapok and coconut shell are abundant, biocompatible, and its full exploration and potential application have received increasing attention in both academic and industrial fields. Based on the structure and properties of kapok and coconut shell, this study shows they are compatible and good absorbent as additional filtration for raw kitchen wastewater pre-treatment process. This study was focused on the performance of the dual functional FOG trap in optimize the FOG contaminant removal process. Parameters measured to evaluate the efficiency of the process were concentration of FOG, pH, COD, BOD, turbidity and suspended solids. The findings show that the efficiency of FOG removal is higher than 50%. The overall qualities of the wastewater improve significantly. In the treatment cycle, the FOG contaminants from the kitchen wastewater are absorbed by the dual functional FOG trap.